2010
DOI: 10.1017/s1368980010001965
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of sports, cycling, walking and overall leisure-time physical activity among postmenopausal women in Germany

Abstract: Objective: Convincing evidence exists for a beneficial effect of physical activity (PA) on health and well-being for elderly women. Nevertheless, many women in Germany are insufficiently physically active. Activity promotion programmes should target women in particular need. Thus, we examined subject-related determinants of PA for postmenopausal women in Germany. Design: Associations of sociodemographic, anthropometric, lifestyle and healthrelated factors with activity since the age of 50 years were assessed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
0
13
0
3
Order By: Relevance
“…The range of participants across included studies was six to 22,050. The majority of the studies were undertaken in Australia ( n = 5) [ 13 , 14 , 20 , 23 , 44 ] and the USA ( n = 5) [ 15 – 18 , 21 ], with one study undertaken respectively in Canada [ 22 ], England [ 45 ], Germany [ 46 ], The Netherlands [ 47 ], New Zealand [ 19 ], Scotland [ 48 ], South Korea [ 49 ] and Sweden [ 50 ]. There were 13 studies that focused on the older adult age group, whilst three studies were non-specific to older adults, but reported age specific data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The range of participants across included studies was six to 22,050. The majority of the studies were undertaken in Australia ( n = 5) [ 13 , 14 , 20 , 23 , 44 ] and the USA ( n = 5) [ 15 – 18 , 21 ], with one study undertaken respectively in Canada [ 22 ], England [ 45 ], Germany [ 46 ], The Netherlands [ 47 ], New Zealand [ 19 ], Scotland [ 48 ], South Korea [ 49 ] and Sweden [ 50 ]. There were 13 studies that focused on the older adult age group, whilst three studies were non-specific to older adults, but reported age specific data.…”
Section: Resultsmentioning
confidence: 99%
“…However more than half of Masters’ participants still played sport in their 20s and 30s and others returned to sport during middle age rather than retirement. Suggests that some prior sport history is important but not all prior participation Competitors believed exercise was more important than non-exercisers, however they had more varied motivation to participate (improved health, in addition to socialisation and competency) than non-sports exercisers and non-exercisers 0.73 [ 46 ] (2010) Quant Cross-sectional 6569 Germany 50–67 Post-menopausal women F Examine the subject-related determinants of physical activity for post-menopausal women PA & sport General sports - Sport participation was significantly associated with occupation (civil servants most popular), so job type can be a determinant for some participants - Also, later in life nulliparous women were less physically active than parous women, and women who had children at a younger age are less likely to participate in sport than older mothers, − Non-indigenous women was strongly associated with low sport participation 0.86 * Research design: Quant = quantitative research methods, Qual = qualitative methods. ** Sex: F = female, m = Male, M&F = both male and female.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…: chorób układu krążenia, otyłości, osteoporozy, demencji, postmenopauzalnemu nowotworowi piersi. Pomaga utrzymać funkcjonalną niezależność i zapobiec upadkom [21]. Jest skuteczna w przypadku łagodzenia negatywnych efektów często stosowanej terapii hormonalnej [22].…”
Section: Minimalizowanie Negatywnych Efektów Menopauzyunclassified
“…Istnieją prace wskazujące na to, że wiele kobiet zaprzestaje ćwiczeń bądź w ogóle ich nie rozpoczyna, gdy słyszy choćby jedną z diagnoz: nadciśnienie tętnicze, cukrzyca, choroba układu krąże-nia [21].…”
Section: Wpływ Aktywności Fizycznejunclassified